Genotypic difference in 137Cs accumulation and transfer from the contaminated field in Fukushima to azuki bean (Vigna angularis). (July 2016) - Win, Khin Thuzar; Oo, Aung Zaw; Kojima, Katsuhiro; Salem, Djedidi; Yamaya, Hiroko; Bellingrath-Kimura, Sonoko Dorothea; Tomooka, Norihiko; Kaga, Akito; Ohkama-Ohtsu, Naoko; Yokoyama, Tadashi
Abstract: The screening of mini-core collection of azuki bean accessions ( Vigna angularis (Willd.) Ohwi & Ohashi) for comparative uptake of 137 Cs in their edible portions was done in field trials on land contaminated by the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident. Ninety seven azuki bean accessions including their wild relatives from a Japanese gene bank, were grown in a field in the Fukushima prefecture, which is located approximately 51 km north of FDNPP. The contamination level of the soil was 3665 ± 480 Bq kg −1 dry weight ( 137 Cs, average ± SD). The soil type comprised clay loam, where the sand: silt: clay proportion was 42:21:37. There was a significant varietal difference in the biomass production, radiocaesium accumulation and transfer factor (TF) of radiocaesium from the soil to edible portion. Under identical agricultural practice, the extent of 137 Cs accumulation by seeds differed between the accessions by as much as 10-fold. Inter-varietal variation was expressed at the ratio of the maximum to minimum observed 137 Cs transfer factor for seeds ranged from 0.092 to 0.009. The total biomass, time to flowering and maturity, and seed yield had negative relationship to 137 Cs activity concentration in seeds. The results suggest that certain variety/varieties of azuki bean which accumulated less 137 Cs in edible portion with preferable agronomic traits are suitable to reduce the 137 Cs accumulation in food chain on contaminated land. Highlights: Varietal difference in the biomass, 137 Cs accumulation and transfer factor was found in azuki. 137 Cs accumulation by seeds differed between the azuki bean accessions by as much as 10 folds. Different accumulation patterns among the azuki bean accessions depends on their growth performance.